Hepcidin suppression in β-thalassemia is associated with the down-regulation of atonal homolog 8 - Supranee Upanan (2018)
© 2017, The Japanese Society of Hematology. Atonal homolog 8 (ATOH8) is defined as a positive regulator of hepcidin transcription, which links erythropoietic activity with iron-sensing molecules. In the present study, we investigated the association between hepcidin and ATOH8 expression in β-thalassemia. We found that inhibition of hepcidin expression in β-thalassemia is correlated with reduced ATOH8 expression. Hepatic hepcidin 1 (Hamp1) and Atoh8 mRNA expression were down-regulated in β-thalassemic mice. Hepcidin (HAMP) and ATOH8 mRNA expression were consistently suppressed in Huh7 cells cultured in medium supplemented with β-thalassemia patient serum. The Huh7 cells, which were transfected with ATOH8-FLAG expression plasmid and cultured in the supplemented medium, exhibited increased levels of ATOH8 mRNA, ATOH8-FLAG protein, pSMAD1,5,8, and HAMP mRNA. Interestingly, over-expression of ATOH8 reversed the effects of hepcidin suppression induced by the β-thalassemia patient sera. In conclusion, hepcidin suppression in β-thalassemia is associated with the down-regulation of ATOH8 in response to anemia. We, therefore, suggest that ATOH8 is an important transcriptional regulator of hepcidin in β-thalassemia.